Danhong Injection Combined With t-PA Improves Thrombolytic Therapy in Focal Embolic Stroke - Li, Min; Zhou, Jing; Jin, Weifeng; Li, Xiaohong; Zhang, Yuyan (Frontiers in Pharmacology, 2018)
Abstract Background Hemorrhagic transformation, neurotoxicity, short treatment time windows, and other defects comprise the major limitations for the thrombolytic therapy. This study is devoted to figure out whether Danhong injection (DHI) combined with tissue-plasminogen activator (t-PA) could extend the treatment time windows and ameliorate brain injury, hemorrhagic complication and BBB disruption after focal embolic stroke. Methods In vitro, the combined concentrations of DHI, t-PA were added to wells reacted with plasminogen and D-Val-Leu-Lys-AMC. We explored the optimum ratio of the combination of DHI plus t-PA by detecting relative fluorescent. In vivo experiments, we firstly investigated the optimal dose of t-PA and Danhong injection for focal embolic stroke. The neurological deficit score, infarct volume and brain edema were assessed. Secondly, we proved that the combination group extended the thrombolytic window for treatment of focal embolic stroke. The neurological deficit score, infarct volume, brain edema and hemorrhagic complication were assessed, while levels of BAX, Bcl-2 and caspase-3 in brain tissue were analysed by real-time polymerase chain reaction. Finally, to ask whether combination therapy with DHI plus t-PA protect the blood-brain barrier in a rat model of focal embolic stroke, neurological deficit score, ELISA, RT-PCR, western blot and fluorescence were used to detect the indicators of blood-brain barrier, such as tight junction protein, blood-brain barrier permeability and related gene expression. Results In vitro, plasmin activity assays showed that combining t-PA with DHI at about 1:1.6 w/v ratio increased by almost 1.4-fold, the plasmin-generating capability of t-PA. In vivo experiments, the results showed that the combination of Danhong injection (4mL/kg) and t-PA (2.5mg/kg) could extend the t-PA treatment time windows to 4.5 h. And the combination t-PA (2.5mg/kg) with DHI (4mL/kg) ameliorated neurological score, cerebral infarction, brain edema, brain hemorrhage and BBB disruption. Conclusions Combination therapy with Danhong injection (4mL/kg) plus t-PA (2.5mg/kg) could extend the t-PA treatment time windows to 4.5 h, ameliorate BBB disruption, reduce infarction, brain swelling and hemorrhage after ischemic stroke.